Analisis Kebutuhan Fasilitas Integrasi Antarmoda di Bandar Udara Tambolaka Kota Sumba Barat Daya - Nuriah Ningrum; Nanik Riananditasari (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
Tambolaka Airport is an airport located in Tambolaka City, Southwest Sumba which is a fairly crowded airport. To realize the role of better Tambolaka Airport services, it is necessary to implement the concept of intermodal transportation integration to facilitate accessibility and passenger movement. This study aims to determine the provision of integration facilities to support intermodal needs at Tambolaka Airport and Planning for the provision of intermodal integration facilities at Tambolaka Airport Primary and secondary data sources were used in the qualitative methodology of this study. Methods used to collect data include documentation, interviews, and observations. Technical and source triangulation are two methods used in data validity procedures. Data reduction, data visualization, and conclusion preparation are some of the data analysis approaches used. The results of this study show that Tambolaka Airport has intermodal transportation such as buses, pick ups, and travel. Tambolaka Airport intermodal integration facilities include airport lounges, pedestrian accessibility, parking lots, and drope zones and Integration development is carried out by developing facilities in the form of pedestrian accessibility and adding bus stops And will be expanded parking from 0.25 Ha to 0.41 Ha.